2009
DOI: 10.18433/j3dw2d
|View full text |Cite
|
Sign up to set email alerts
|

HCV Protease Inhibitory, Cytotoxic and Apoptosis-Inducing Effects of Oleanolic Acid Derivatives

Abstract: -Purpose. To evaluate oleanolic acid derivatives on liver disease related bioactivities, 29 oleanolic acid derivatives of several series were tested for their inhibitory activity on hepatitis C viral protease as well as for their cytotoxic and apoptosis-inducing effects on Hep G2 cells. Results. The amino derivatives (17-19) showed potent cytotoxicity. The -amino isomer (18) showed strong apoptosis-inducing effect and exhibited more distinct cytotoxicity than the -isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
(20 reference statements)
2
20
0
Order By: Relevance
“…The major compound of L. salicaria, oleanolic acid (8), is a signifi cant antitumour agent against the HCT15 cell line (Li et al, 2002). Finally, triterpene derivatives were found to inhibit the growth of HepG2 cells in a concentration-dependent manner (Ma et al, 2009). Antiproliferative and apoptosis-inducing activities of β-sitosterol (11) in human leuke- (Park et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major compound of L. salicaria, oleanolic acid (8), is a signifi cant antitumour agent against the HCT15 cell line (Li et al, 2002). Finally, triterpene derivatives were found to inhibit the growth of HepG2 cells in a concentration-dependent manner (Ma et al, 2009). Antiproliferative and apoptosis-inducing activities of β-sitosterol (11) in human leuke- (Park et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer has become one of the most devastating diseases of humankind in the world (Ma et al, 2009). Natural products or their related components constitute more than half of the drugs used in cancer therapy (Newman and Cragg, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…OA (17) was also found to be an HCV protease inhibitor. 91 Based on this lead compound, 29 OA derivatives were synthesized and tested for their inhibitory activity on hepatitis C viral protease. The derivatives of dicarboxylic acid hemiesters showed potent activity against HCV protease.…”
Section: Hcv Protease Inhibitorsmentioning
confidence: 99%
“…This compound is reported to have a wide array of biological properties including anti-nociceptive, anti-inflammatory, anti-cancer, anti-diabetic, hepatoprotective, antioxidant, and immunomodulatory properties [5][6][7]. Indeed in countries such as China, OA is sold as a dietary supplement and is supplied as an over-the-counter drug for treatment of liver diseases [8]. However, although OA seems to have much therapeutic potential, the use of this compound has been limited by its poor solubility in aqueous solutions [9] and its low bioavailability on oral treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the search for semisynthetic derivatives of the compound which might have improved solubility and bioavailability on oral treatment as well as better effects. Indeed, some amino acid derivatives of OA have shown potent cytotoxic and apoptosis-inducing effects on Hep G2 cells compared to OA [8]. In a recent paper, Habila et al [11] showed that C-3 modification of OA was accompanied by improved anti-microbial properties compared to the parent compound indicating that molecular modification of compounds obtained from natural products could provide more potent molecules for therapeutic use [12,13].…”
Section: Introductionmentioning
confidence: 99%